Comparing the efficacy of glucocorticoids and anti-VEGF in treating diabetic macular edema: systematic review and comprehensive analysis - Cheng, Zhi’ang; Liu, Xiaoyong (Frontiers in Endocrinology, 2024)
The aim of this study was to better understand the efficacy of various drugs, such as glucocorticoids and anti-vascular endothelial growth factors (VEGF), in the treatment of diabetic macular edema (DME), and to evaluate various clinical treatment regimens consisting of different therapeutic measures. This study included randomized controlled trials up to February 2023 comparing the efficacy of corticosteroid-related therapy and anti-VEGF therapy. PubMed, the Cochrane Library, and Embase were searched, and the quality of the studies was carefully assessed. Finally, 39 studies were included. Results at 3-month follow-up showed that intravitreal injection of bevacizumab (IVB) + triamcinolone acetonide (TA) was the most beneficial in improving best-corrected visual acuity and reducing the thickness of macular edema in the center of the retina in patients with DME. Results at 6-month follow-up showed that intravitreal dexamethasone (DEX) was the most effective in improving patients' best-corrected visual acuity and reducing the thickness of central macular edema. Overall, IVB+TA was beneficial in improving best-corrected visual acuity and reducing central macular edema thickness over a 3-month follow-up period, while DEX implants had a better therapeutic effect than anti-VEGF agents at 6 months, especially the patients with severe macular edema and visual acuity impaired.